EMPLOYEE PERFORMANCE STUDIES: ANTECEDENTS OF WORK DISCIPLINE, WORK MOTIVATION, AND JOB TRAINING - Syarifuddin Hasibuan, Jasman; Lesmana, M. Taufik; Permata Sari, Ainun (RADJA PUBLIKA, 2021)
The purpose of this study was to determine and analyze whether Work Discipline, Work Motivation, and Job Training together (simultaneously) or alone (partial) had an effect on Employee Performance at PT. Telekomunikasi Indonesia Tbk Medan Branch.The approach used in this study is an associative approach. The population and sample in this study were all employees of PT. Telekomunikasi Indonesia Tbk Medan Branch in the Data and Management section totaling 50 people using a saturated sample. The data collection technique in this study used a questionnaire technique (questionnaire). The data analysis technique in this study uses the Classical Assumption Test, Multiple Regression, Hypothesis Testing (t Test and F Test), and Coefficient of Determination. Data processing in this study used a computer software program Statistical Package for the Social Sciences (SPSS) version 26.00.The results showed that partially work discipline had a positive and significant effect on employee performance at PT. Telekomunikasi Indonesia Tbk Medan Branch. Partially it is known that motivation has a positive and significant effect on employee performance at PT. Telekomunikasi Indonesia Tbk Medan Branch. Likewise with job training which has a positive and significant impact on employee performance at PT. Telekomunikasi Indonesia Tbk Medan Branch. Meanwhile, simultaneously this research proves that work discipline, work motivation and job training have a positive and significant effect on employee performance at PT. Telekomunikasi Indonesia Tbk Medan Branch.